Determination of Total Selenium in Infant Formulas: Comparison of the Performance of FIA and MCFA Flow Systems - Mariela Pistón; Moisés Knochen (International Journal of Analytical Chemistry)
Two flow methods, based, respectively, on flow-injection analysis (FIA) and on multicommutated flow analysis (MCFA), were compared with regard to their use for the determination of total selenium in infant formulas by hydride-generation atomic absorption spectrometry. The method based on multicommutation provided lower detection and quantification limits (0.08 and 0.27 μg L−1 compared to 0.59 and 1.95 μ L−1, resp.), higher sampling frequency (160 versus. 70 samples per hour), and reduced reagent consumption. Linearity, precision, and accuracy were similar for the two methods compared. It was concluded that, while both methods proved to be appropriate for the purpose, the MCFA-based method exhibited a better performance.